The Psychopath Phenomenon Reflected InGillian Flynn 'S Gone Girl Novel (2012):A Psychoanalytic Approach - Nur Wahid, Rosin Novaditya, Dr. M. Thoyibi, M.S, Siti Fatimah, A M. Hum (2016)
This research is about The Psychopath Phenomenon Reflected in Gillian Flynn's Gone Girl novel (2012) which is analyzed by using Psychoanalytic Approach. The objectives of this study are to describe the characteristic of psychopath, to analyze types of psychopath, to analyze the cause of being of psychopath, and to understand why the author opened psychopath to the public. This research is a qualitative research. The primary data of this research is Gone Girl (2012) a novel by Gillian Flynn. The secondary data are some selected references and material related to the study. The researcher displays four conclusions in this research. Firstly, everybody can be a psychopath and have five characteristics namely, lack of remorse, grandiosity, compulsive lying, manipulative, anti - social behavior. Secondly, there are two types of psychopath. Namely Con Artist and The Victim. Con artist is a psychopath who is good at manipulating, fluent lying and distorting the facts, and The Victim a psychopath who uses sex as a hook for achieving the goal. Thirdly, the causes of psychopath. Family problem is one of the causes someone to be a psychopath. And the last, Gillian Flynn take psychopath in her books to show the dark side of woman.